TINDAKAN TAX AVOIDANCE DILIHAT DARI KONSERVATISME AKUNTANSI, LEVERAGE, DAN UKURAN PERUSAHAAN - Denny Putri Hapsari (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of accounting conservatism on tax avoidance, leverage on tax avoidance and company size on tax avoidance in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2015-2020 period. This research was conducted using quantitative methods with an associative approach. The population of this study was 30 companies and 14 companies were sampled using the purposive sampling method. Data analysis using SPSS version 25. Based on the results, it can be partially concluded that: 1) Accounting Conservatism has a significant influence on Tax Avoidance with a significance value of 0.009, 2) Leverage has no significant influence on Tax Avoidance has a significance value of 0.763, 3) Company Size there is a significant influence on Tax Avoidance has a significance value of 0.049.